2021
DOI: 10.1177/10760296211063877
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anticoagulant Activity of Tissue Factor Pathway Inhibitor Measured by a Novel Functional Assay for Predicting Deep Venous Thrombosis in Trauma Patients: A Prospective Nested Case-Control Study

Abstract: Objective Deep venous thrombosis (DVT) is a common complication in patients with traumatic injury. Tissue factor pathway inhibitor (TFPI) is a natural anticoagulant protein in the extrinsic coagulation pathway. However, the relationship between DVT after trauma and the anticoagulant activity of TFPI remains unclear. In this prospective study, we investigated the role of TFPI in trauma patients with DVT to evaluate whether the anticoagulant activity of TFPI measured by a new functional assay can be used to help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(47 reference statements)
0
3
2
Order By: Relevance
“… 24 , 25 This along with the upregulation of tissue factor incurred in surgical endothelial manipulation and the observed thrombotic rate suggests needed balance when weighing andexanet alfa use and anticoagulation reinitiation. 29 , 30 Despite the high rate of thromboischemic events, obtained postreversal TEG parameters did not detect or suggest hypercoagulability in the current study. It may also be worth noting that two of the six patients presenting without active bleeding who received andexanet alfa as an off‐label indication developed a thromboischemic complication.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“… 24 , 25 This along with the upregulation of tissue factor incurred in surgical endothelial manipulation and the observed thrombotic rate suggests needed balance when weighing andexanet alfa use and anticoagulation reinitiation. 29 , 30 Despite the high rate of thromboischemic events, obtained postreversal TEG parameters did not detect or suggest hypercoagulability in the current study. It may also be worth noting that two of the six patients presenting without active bleeding who received andexanet alfa as an off‐label indication developed a thromboischemic complication.…”
Section: Discussioncontrasting
confidence: 81%
“…Andexanet alfa has been suggested to induce hypercoagulability through inhibition of TFPI, the main regulator of the tissue factor pathway 24,25 . This along with the upregulation of tissue factor incurred in surgical endothelial manipulation and the observed thrombotic rate suggests needed balance when weighing andexanet alfa use and anticoagulation reinitiation 29–30 . Despite the high rate of thromboischemic events, obtained postreversal TEG parameters did not detect or suggest hypercoagulability in the current study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“… 46 In previous studies, our team observed significantly increased levels of thrombomodulin and tissue factor pathway inhibitor in trauma patients with DVT. 47 In addition, the content of endothelial tissue factor MPs was increased significantly (results not published), which indicated endothelial dysfunction in trauma patients with DVT. Overall, the uptake of vesicles by endothelial cells with the concomitant occurrence of endothelial dysfunction and the role they play in DVT in trauma patients deserve further exploration.…”
Section: Discussionmentioning
confidence: 97%
“…Cao et al compared clinical data between people who developed DVT after fracture with those who did not develop DVT after fracture and with healthy controls. They observed that the level of PT was significantly increased in the DVT group, and they noted that the optimal threshold for PT to diagnose DVT was 12.05s, with a sensitivity of 72.92% and specificity of 47.92% (AUC = 0.617, 95% CI 0.505-0.730, p = 0.048) [39]. Above all, the predictors included in our prediction model in this study were all inflammatory in previous studies, proving the validity of our study.…”
Section: Discussionmentioning
confidence: 99%